Marriage Restrictions among Election Organizers: Reconstructing Legal Justifications through Constitutional Rights, Maslahah Mursalah, and Institutional Integrity - Julian, Kukuh (SMART: Journal of Sharia, Traditon, and Modernity, 2026)
The prohibition of marriage between election organizers within the General Elections Commission (KPU) and the Election Supervisory Agency (Bawaslu) has generated debate because it intersects with the constitutional right to form a family and the need to safeguard the institutional integrity of elections. This study analyzes the normative basis, legal justification, and relevance of this policy from the perspectives of positive law and maslahah mursalah. This research employs an empirical-juridical method with a qualitative approach through literature review, documentation, and in-depth interviews with election organizers in Lampung Province. The data were analyzed using the theories of maslahah mursalah, electoral integrity, and the principle of conflict of interest. The findings indicate that the prohibition of marriage may obtain legitimacy as an instrument for preventing conflicts of interest when implemented proportionally, without eliminating the substance of constitutional rights, and when directed toward protecting the public interest, the integrity of election organizers, and public trust in election results. This study recommends improving conflict-of-interest regulations through ethical governance, ethical oversight, and clearer limitations on public office in order to maintain a fair and proportional balance between individual rights and democratic interests.